Cinematography Design of Integrated Service Video Documentation - B, Sahrul; Fathahillah, Fathahillah; Yasdin, Yasdin (Center of Research and Innovation Strengthen LP2M UNM, 2023)
This study aims to find out how the scene is in the integrated service video documentation, to know the cinematographic techniques used in the integrated service video documentation, and to find out the responses of respondents to the integrated research video documentation. This study used descriptive qualitative method. The method of data collection is by means of observation, documentation, and questionnaires. Data analysis used is data reduction, and the feasibility percentage scale. The results of this study indicate that: (1) The scan applied to the 2022 community service video media is the initial scan showing the Phinisi tower, the next scan showing departure to the service location, the next scan showing the servant at the service location, and the closing scan showing the logo animation LP2M. (2) The cinematographic technique that is often used in this community service video media uses an objective camera angel and a subjective camera angel to capture every scene in the community service video media that is made. Low angel level, Eye level angle, High level camera, Extreme long shot, Very long shot, Medium long shot, Close up, and Medium close up. The composition in the dedication video media